Clinical Dental Faculty Members' Perceptions of Diagnostic Errors and How to Avoid Them. Issue 4 (1st April 2018) - Nikdel, Cathy; Nikdel, Kian; Ibarra-Noriega, Ana; Kalenderian, Elsbeth; Walji, Muhammad F.
Abstract : Diagnostic errors are increasingly recognized as a source of preventable harm in medicine, yet little is known about their occurrence in dentistry. The aim of this study was to gain a deeper understanding of clinical dental faculty members' perceptions of diagnostic errors, types of errors that may occur, and possible contributing factors. The authors conducted semi‐structured interviews with ten domain experts at one U.S. dental school in May–August 2016 about their perceptions of diagnostic errors and their causes. The interviews were analyzed using an inductive process to identify themes and key findings. The results showed that the participants varied in their definitions of diagnostic errors. While all identified missed diagnosis and wrong diagnosis, only four participants perceived that a delay in diagnosis was a diagnostic error. Some participants perceived that an error occurs only when the choice of treatment leads to harm. Contributing factors associated with diagnostic errors included the knowledge and skills of the dentist, not taking adequate time, lack of communication among colleagues, and cognitive biases such as premature closure based on previous experience. Strategies suggested by the participants to prevent these errors were taking adequate time when investigating a case, forming study groups, increasing communication, and putting more emphasis on differential diagnosis. These interviews revealed differing perceptions of dental diagnostic errors among clinical dental faculty members. To address the variations, the authors recommend adopting shared language developed by the medical profession to increase understanding.